2018
DOI: 10.1111/ctr.13453
|View full text |Cite
|
Sign up to set email alerts
|

Risk of adverse maternal and fetal outcomes during pregnancy in living kidney donors: A matched cohort study

Abstract: Background: We examined the risk of adverse pregnancy outcomes in primiparous kidney donors compared to matched controls. Methods: Fifty-nine women with a history of kidney donation prior to their first pregnancy with normal renal function and no history of kidney disease, diabetes or chronic hypertension were matched 1:4 by age (within 2 years) and race to women with two kidneys using data from an integrated healthcare delivery system. Adverse pregnancy outcomes were defined as preterm delivery (delivery < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…30 Three studies compared outcomes to the general population. 26 The risk of pre-eclampsia/eclampsia was not statistically different between the groups (OR: 2.96, 95% CI: 0.98-8.94, p = .06). LKD ≤30 years, had a four-fold increased risk of pre-eclampsia/eclampsia (OR: 4.09, 95% CI: 1.07-15.59, p = .04).…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 83%
See 1 more Smart Citation
“…30 Three studies compared outcomes to the general population. 26 The risk of pre-eclampsia/eclampsia was not statistically different between the groups (OR: 2.96, 95% CI: 0.98-8.94, p = .06). LKD ≤30 years, had a four-fold increased risk of pre-eclampsia/eclampsia (OR: 4.09, 95% CI: 1.07-15.59, p = .04).…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 83%
“…Davis et al (2019) using the Intermountain Healthcare Enterprise Data Warehouse, compared pregnancy outcomes in 59 LKD (≥2 years after donation) with 236 age‐ and race‐matched controls 26 . The risk of pre‐eclampsia/eclampsia was not statistically different between the groups (OR: 2.96, 95% CI: 0.98–8.94, p = .06).…”
Section: Resultsmentioning
confidence: 99%
“…The Ontario study found an increased risk of gestational hypertension or preeclampsia in donors > 32 years of age 13 . By contrast, recent study reported that first childbirth before 30 years of age is a risk factor for preeclampsia and eclampsia in donors 28 . In this study, multivariable analysis revealed that primipara and time from donation to delivery (< 5 years) were significantly associated with increased risk of preeclampsia.…”
Section: Discussionmentioning
confidence: 76%
“…Independently from kidney function, the presence of kidney damage, or a reduction in kidney tissue, it is now known to be associated with an increased incidence of adverse pregnancy outcomes, including preterm delivery, preeclampsia, the hypertensive disorders of pregnancy, and giving birth to a small-for-gestational-age (SGA) baby [ 4 , 5 , 6 ]. This is also true of those who have a healthy single kidney (as is the case of kidney donors), and is observed, among others, in patients with kidney stones, and in cases with a previous episode of acute kidney injury (AKI), even after complete normalization of renal function [ 7 , 8 , 9 , 10 ]. The risk of adverse pregnancy outcomes is also higher in patients with kidney damage without hypertension, proteinuria, or loss of kidney function, and are further modulated by these three elements.…”
Section: Introductionmentioning
confidence: 99%